Peran Islamic Social Finance dalam Membangun Resiliensi Ekonomi Masyarakat Muslim Indonesia pada Krisis Global - Malta Anna (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2026)
Geopolitical conflicts in the Middle East over recent years have exerted significant pressure on the global economy through rising energy prices, disruptions in supply chains, and increasing inflationary pressures. These impacts have also been felt in Indonesia, particularly through declining household purchasing power, rising living costs, and growing economic vulnerability among low-income communities. In this context, Islamic Social Finance (ISF), which encompasses zakat, infaq, sadaqah, and waqf, possesses considerable potential as both a social protection mechanism and an instrument for strengthening community economic resilience. This study aims to explore the role of Islamic Social Finance in enhancing the economic resilience of Indonesian Muslim communities amid the global crisis triggered by conflicts in the Middle East. The research employs a qualitative approach using an exploratory case study design. Data were collected through in-depth interviews, observations, documentation, and reviews of institutional reports and relevant literature. The participants consisted of zakat and waqf institution managers, program beneficiaries, academics, and community representatives. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data reduction, data display, and conclusion drawing. The findings reveal that institutions such as BAZNAS, zakat organizations (LAZ), and waqf administrators play a significant role in maintaining household economic stability through two primary approaches: consumptive assistance and productive empowerment programs. While consumptive support helps households meet basic needs during periods of inflation, productive programs such as business capital assistance, entrepreneurship training, and mentoring contribute to sustainable income recovery. The study further finds that institutional capacity, public literacy, digital transformation, and government support are critical determinants of ISF effectiveness. Theoretically, ISF functions as a redistributive economic mechanism consistent with economic resilience theory and the principles of maqasid al-shariah. Practically, strengthening collaboration among government institutions, Islamic philanthropic organizations, and communities is essential to optimizing ISF as an integral component of Indonesia’s social protection system.